SCREENING OF PROMISING CLONES IN EARLY CLONAL GENERATIONS FROM POOL OF SACCHARUM COMPLEX HYBRIDS - CHANDRAKANT, -; KANT, RAVI; SINGH, P.K. (Annals of Agricultural Research, 2014)
Eighty four clones including three checks in first and second consecutive clonal generations were undertaken with the objective to identify reliable yield attributing traits for formulation of selection indices and selection of suitable clones in early clonal generation. A consistent trend for the significance of mean sum of square due to checks, entries, check vs. entries, range of variation and coefficient of variation was observed in both clonal generations. Correlation coefficient study revealed that only three quantitative traits i.e., number of shoots at 120 days, number of millable cane at harvest and single cane weight showed consistent trend of significant association with cane yield in both the clonal generations. Path coefficient analysis revealed that number of millable cane at harvest and single cane weight were major direct contibutor in both clonal generations. Multiple regression analysis revealed that single cane weight act as most reliable traits in predicting performance in early clonal generations. Preliminary selection in early clonal generation should be based on quantitative traits i.e. single cane weight, number of shoots at 120 days and number of millable canes and quality traits should be delayed to latter generation till the character stabilize.